Understanding the effect of retirement on health using regression discontinuity design - Peter Eibich (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper estimates the causal effect of retirement on health, health behavior, and healthcare utilization. Using Regression Discontinuity Design to exploit financial incentives in the German pension system for identification, I investigate a wide range of health behaviors (e.g. alcohol and tobacco consumption, physical activity, diet and sleep) as potential mechanisms. The results show a long-run improvement in health upon retirement. Relief from work-related stress and strain, increased sleep duration and more frequent physical exercise seem to be key mechanisms through which retirement affects health. Moreover, the improvement in health caused by retirement leads to a reduction in healthcare utilization.
Keywords: I12; J14; J26; 330; retirement; health; regression discontinuity design; health behavior; healthcare